2011
DOI: 10.4103/0974-2727.78564
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycetes Mycetoma

Abstract: Mycetoma is a chronic infection, frequently seen in tropical and sub-tropical countries and is considered as an occupational disease. Nocardia species though it can infect immunocompetent individuals, it most commonly affects immunocompromised patients. A 50-year-old male, farmer presented to our hospital with serosanguineous discharging swelling over the dorsum of right foot. We have isolated Nocardia asteroides from the tissue sample. Speciation of this isolate was carried out based on phenotypic methods. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Increase in the infections caused by these organisms, with different clinical forms of systemic and disseminated forms of nocardiosis in transplant recipients, tuberculosis, liver cirrhosis, cancer, diabetes, AIDS and patients under treatment with immunosuppressive drugs and broad spectrum antibiotics in the world, reveals more importance of isolation and identification of these agents [2,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Various studies have shown that identification and isolation of these agents in soil of different areas help to diagnose nocardiosis [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Increase in the infections caused by these organisms, with different clinical forms of systemic and disseminated forms of nocardiosis in transplant recipients, tuberculosis, liver cirrhosis, cancer, diabetes, AIDS and patients under treatment with immunosuppressive drugs and broad spectrum antibiotics in the world, reveals more importance of isolation and identification of these agents [2,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Various studies have shown that identification and isolation of these agents in soil of different areas help to diagnose nocardiosis [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Mycetoma is a chronic infection and is considered as an occupational disease. 1 Mycetoma infection can be caused by fungi or bacteria and is, respectively, called as mycotic mycetoma and actinomycetoma.…”
Section: Discussionmentioning
confidence: 99%
“…The disease can spread to almost any organ of the body but the pulmonary system remains the most frequent primary site of involvement. 1 In recipients of solid organ transplant, nocardia infection has been well described in kidney, heart, and liver recipient. 4 As inhalation is the primary route of bacterial exposure, pulmonary nocardiosis is the most common clinical presentation of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Actinomycetoma may be due to Actinomadura madurae, Actinomadura peliietieri, Streptomyces somaliensis, Nocardia species [1]. John Gill in 1842 described its clinical features for the first time and named it "madura foot" after the region of Madurai in India, where it was first identified [2]. Mycetoma occurs most often in people who work in rural areas, usually in farmers, field workers where they are exposed to cactus thorns or acacia trees that contain etiologic agents that normally live as saprophytes [1].…”
Section: Introductionmentioning
confidence: 99%